2018
DOI: 10.1055/a-0677-2720
|View full text |Cite
|
Sign up to set email alerts
|

MetS Risk Score: A Clear Scoring Model to Predict a 3-Year Risk for Metabolic Syndrome

Abstract: Although several risk factors for metabolic syndrome (MetS) have been reported, there are few clinical scores that predict its incidence. Therefore, we created and validated a risk score for prediction of 3-year risk for MetS. Three-year follow-up data of 4395 initially MetS-free subjects, enrolled for an annual physical examination from Wenzhou Medical Center were analyzed. Subjects at enrollment were randomly divided into the training and the validation cohort. Univariate and multivariate logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…Consequently, a formal meta-analysis was precluded due to the heterogeneity of data particularly regarding the diverse demographics of the studied participants and different components of the scores. Surprisingly, the observed incidence/prevalence of MetS at the end of the study is not reported in nearly a third (twenty-nine per cent) of the studies [24,28,31,37,41,42]. For those that reported it, the prevalence/ incidence of MetS ranged from as little as one per cent to as high as thirty-seven per cent (median is thirteen per cent).…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Consequently, a formal meta-analysis was precluded due to the heterogeneity of data particularly regarding the diverse demographics of the studied participants and different components of the scores. Surprisingly, the observed incidence/prevalence of MetS at the end of the study is not reported in nearly a third (twenty-nine per cent) of the studies [24,28,31,37,41,42]. For those that reported it, the prevalence/ incidence of MetS ranged from as little as one per cent to as high as thirty-seven per cent (median is thirteen per cent).…”
Section: Resultsmentioning
confidence: 79%
“…Of these 24 papers, 22 report about the development of one or more risk model or score [24][25][26][27][28][29][30][31][32][33][34][35]37,38,[40][41][42][43][44][45][46][47], and 2 studies report about the development and external validation of one or more risk model or scores on an external population [36,39].Overall, the 24 studies reported 40 models, out of which 24 models were selected for full data extraction. The rest (16 models) were not selected, either because they were judged to be minimally different from the reported ones or they were not the preferred models by the authors or they were significantly deficient in details or statistical reporting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, out of the 27 included papers, 25 report about the development of one or more risk model or score [19][20][21][22][23][24][25][26][27][28][29][30]32,33,[35][36][37][38][39][40][41][42][43][44][45], and 2 studies report about the development and validation of one or more risk model or scores on an external population [31,34]. Overall, the 27 studies reported 43 models, out of which 27 models were selected for full data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the target population, more risk scores were reported in adults than in children or adolescents. Of the 27 included models, 17 focused on adult subjects [19,20,24,[26][27][28][29][30][31][32][33][36][37][38][39]42,45], while 10 targets children and adolescents [21][22][23]25,34,35,40,41,43,44].…”
Section: Mets Risk Models or Scores For Childrenmentioning
confidence: 99%